Multiscale distribution patterns of pelagic rafts of sargasso (Sargassum spp.) in the Mexican Caribbean (2014–2020) - Uribe-Martínez, Abigail; Berriel-Bueno, Diana; Chávez, Valeria; Cuevas, Eduardo; Almeida, Karla L.; Fontes, Jassiel V. H.; van Tussenbroek, Brigitta I.; Mariño-Tapia, Ismael; Liceaga-Correa, Maria de los Ángeles; Ojeda, Elena; Castañeda-Ramírez, D. Gerardo; Silva, Rodolfo (Frontiers in Marine Science, 2022)
As the biomass of pelagic Sargassum spp. increased across the North Atlantic equatorial recirculation region from 2011, massive rafts of sargasso appeared in the Western Caribbean in 2015, 2018, 2019, and 2020. These events raised concerns regarding their negative consequences on the environment, local income, and human wellbeing in the Mexican Caribbean. As adequate monitoring and analysis tools are needed for designing in-water and on-beach control strategies to reduce potential negative impacts, more robust and spatially explicit information is needed in order to improve sargassum management and focus restoration efforts. In this paper, we offer a spatiotemporal multiscale description of sargasso distribution and dynamics for 2014-2020 in the Mexican Caribbean: (1) for the entire region (millions of square kilometres); (2) at local scale (thousands of square kilometres) evaluating the dynamics inside the reef lagoon at Puerto Morelos, Mexico, and finally, (3) specific beach observations (hundreds of square kilometres) derived from data on beach cleaning volumes. Fifteen regions in the Mexican Caribbean, with different sargasso dispersions and on-shore accumulations, were evaluated. Images from a coastal video monitoring station near Puerto Morelos reef lagoon showed that the massive sargasso beaching was associated with low energy conditions (Hs < 0.25 m, wind speed< 4m/s, neap tide), while non-accumulation of sargasso on the beach occurred under high energy conditions (Hs > 0.4 m, wind speed = 8 m/s, spring tide). Time series analyses of Sargasso beaching showed different periods of historic maximum sargasso coverage over July-October 2018 and others in January-February 2019. Wind and wave regimes influenced sargasso in distinct ways, depending on the coastal section, probably related to coastline aspect, oceanic regime or the extent of the continental platform.